1991
DOI: 10.1121/1.401923
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of locus equations as a source of relational invariance for stop place categorization

Abstract: Locus equations were investigated as a potential metric capable of illustrating relational invariance for place of articulation in voiced initial stop consonants independently of vowel context. Locus equations are straight line regression fits to data points formed by plotting onsets of F2 transitions along the y axis and their corresponding midvowel nuclei along the x axis. Twenty subjects, 10 male and 10 female, produced/b/v/t/,/d/v/t/, and/g/v/t/tokens for ten vowel contexts. Each CVC token was repeated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
142
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 213 publications
(153 citation statements)
references
References 28 publications
9
142
1
1
Order By: Relevance
“…Our findings thus generally concur with those ofthe synthetic speech experiments by Fruchter and Sussman (1997) and Eek and Meister (1995), who found that the regions in F2 space corresponding to high-proportion selections of each consonant only partially overlapped with their respective locus equation lines. Thus, in response to the research questions posed by Sussman et al (1991), we found that proximity to locus equation lines bears only a gross relationship to perceptual consonant classification.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Our findings thus generally concur with those ofthe synthetic speech experiments by Fruchter and Sussman (1997) and Eek and Meister (1995), who found that the regions in F2 space corresponding to high-proportion selections of each consonant only partially overlapped with their respective locus equation lines. Thus, in response to the research questions posed by Sussman et al (1991), we found that proximity to locus equation lines bears only a gross relationship to perceptual consonant classification.…”
Section: Discussionmentioning
confidence: 81%
“…However, given that the F2 transition is proposed as a primary cue, and one for which evolution shaped the auditory perceptual system, it might be expected to have more predictive strength than was found here. A different sort of account could be devised in which F2, F3, and burst information are not treated as independent cues (Dorman, Studdert-Kennedy, & Raphael, 1977), but rather are considered together; for example, a model could be based on prototypes defined in a three-dimensional space ofF2 ons' F2yowel' and F3 0ns (Lindblom, 1990;Sussman, 1991). We believe, however, that the OOC hypothesis cannot apply to such a model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations